2015
DOI: 10.1016/j.psym.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Postoperative Subsyndromal Delirium

Abstract: Background Whether postoperative subsyndromal delirium (SSD) is a separate syndrome from delirium and has clinical relevance is not well understood. Objectives We sought to investigate SSD in older surgical patients and to determine its prognostic significance. Methods We performed a prospective cohort study of patients aged ≥65 years of age scheduled for noncardiac surgery. Postoperative delirium was determined using the Confusion Assessment Method. SSD was defined as the presence of at least one out of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 18 publications
(26 reference statements)
1
71
2
Order By: Relevance
“…Described by Schieveld et al (6), children with emerging delirium have an atypical presentation characterized by anxiety and disturbances in cognition, but do not develop full delirium. Future studies are needed to determine if pediatric emerging/subsyndromal delirium places children at risk for additional morbidity as described in adult literature (33). We identified 41 patients who had only one positive CAP-D(R) rating and we conceptualized these cases as emerging delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Described by Schieveld et al (6), children with emerging delirium have an atypical presentation characterized by anxiety and disturbances in cognition, but do not develop full delirium. Future studies are needed to determine if pediatric emerging/subsyndromal delirium places children at risk for additional morbidity as described in adult literature (33). We identified 41 patients who had only one positive CAP-D(R) rating and we conceptualized these cases as emerging delirium.…”
Section: Discussionmentioning
confidence: 99%
“…While subsyndromal symptoms are less severe than those seen in delirium, they are predictors for adverse outcomes, increased falls postoperatively, including increased lengths of hospital stays and long-term care admissions, and higher mortality rates (Cole, McCusker, Dendukuri, & Han, 2003; Cole et al, 2011; DeCrane, Culp, & Wakefield, 2012). Some have concluded that the presence of even one core symptom of delirium in an older adult is sufficient enough to result in an increase in the length of hospital stay and/or a decline in functional status (Shim, DePalma, Sands, & Leung, 2015). Identification of patients who are at risk for subsyndromal delirium should be made prior to surgery so prevention strategies can be initiated.…”
Section: Introductionmentioning
confidence: 99%
“…Given that one subsyndromal delirium symptom may be sufficient to cause increased lengths of hospital stay, a decline in functional status, and an increased risk for development of delirium (Shim et al, 2015), understanding the significance of subsyndromal delirium seemed essential in identifying high-risk patients for prevention and early detection to minimize adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Subsyndromal delirium (SSD) is thought to represent a subthreshold state related to delirium and associated with poor posthospitalization outcomes similar to those associated with delirium [1][2][3][4][5][6][7][8]. However, it lacks a standardized definition, even in Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5) [9] where it is only noted as an "attenuated delirium syndrome" without specific criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Early attempts at categorical delineation of SSD required the presence of fewer symptoms than for syndromal delirium, although the specific symptoms were arbitrarily selected, did not involve severity determinations, and required only one or two symptoms that had not been empirically chosen for specificity to the delirium syndrome [1,3,6,7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%